2016
DOI: 10.3109/17483107.2016.1173730
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical evaluation of the automatic stance-phase lock-controlled prosthetic knee joint in young adults with unilateral above-knee amputation

Abstract: Potential benefits of the ASPL knee were identified in this study by functional measures, questionnaires and user feedback, but not changes in activity or the PEQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…There was good correlation between the SEW values for level walking and other clinical outcome measures. Andrysek (2017) [ 64 ] Long-term clinical evaluation of the automatic stance-phase lock-controlled prosthetic knee joint in young adults with unilateral above-knee amputation 10 participants (All AK) Power Walker EX-510 (P. Anterior/ medial of thigh) Steps/day (2 weeks) Compare the ASPL knee to the WBA knee on step count, walking speed and energy expenditure. Participants did not tend to alter their walking speed or step count with the ASPL knee, but a reduction in energy expenditure was found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was good correlation between the SEW values for level walking and other clinical outcome measures. Andrysek (2017) [ 64 ] Long-term clinical evaluation of the automatic stance-phase lock-controlled prosthetic knee joint in young adults with unilateral above-knee amputation 10 participants (All AK) Power Walker EX-510 (P. Anterior/ medial of thigh) Steps/day (2 weeks) Compare the ASPL knee to the WBA knee on step count, walking speed and energy expenditure. Participants did not tend to alter their walking speed or step count with the ASPL knee, but a reduction in energy expenditure was found.…”
Section: Resultsmentioning
confidence: 99%
“…The 27 papers on comparing interventions for lower-limb prosthesis users mostly compared prosthetic components, rather than comparing lifestyle interventions. Studies compared different sockets [ 66 , 79 , 84 ], suspension systems [ 68 , 78 ], knees [ 12 , 64 , 72 74 , 87 ], pylons [ 65 ] and feet [ 63 , 70 , 76 , 82 , 83 , 88 , 99 ]. One study compared knees and pylons [ 77 ], and one compared torsion and rigid adapters [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 27 papers on comparing interventions for lower-limb prosthesis users mostly compared prosthetic components, rather than comparing lifestyle interventions. Studies compared different sockets, 66,79,84 suspension systems, 68,78 knees, 12,64,[72][73][74]87 pylons 65 and feet. 63,70,76,82,83,88,100 One study compared knees and pylons, 77 and one compared torsion and rigid adapters.…”
Section: Figure 1 Flow Chart Of Selection and Sorting Methodsmentioning
confidence: 99%
“…This may be explained by an assertion of Seymour (2002) that the more proximal the amputation, more energy is demanded from the cardiovascular and pulmonary systems, and the less can the energy demand be satisfied for functional and social activities. Moreover, the absence of a functional knee joint amongthe above-knee amputation group may also be a contributing factor to their functional limitation because the presence of the knee joint in individuals with amputation was reported to improve stability and enhance function (Andrysek et al, 2016). It was found that there was a significantly better level of social functioning and participation among individuals using prosthetic mobility aids compared to their counterparts with non-prosthetic mobility aids (Table 7).While prosthetic users could move easily around their homes and in the community, non-prosthetic users -particularly those using wheelchairs -may find the environment as an obstacle to social participation.…”
Section: Participants' Levels Of Social Functioning and Participationmentioning
confidence: 99%